(040)‐Crystal Facet Engineering of BiVO4 Plate Photoanodes for Solar Fuel Production. Issue 4 (10th December 2015) - Kim, Chang Woo; Son, Young Seok; Kang, Myung Jong; Kim, Do Yoon; Kang, Young Soo
Abstract : A (040)‐crystal facet engineered BiVO4 ((040)‐BVO) photoanode is investigated for solar fuel production. The (040)‐BVO photoanode is favorable for improved charge carrier mobility and high photocatalytic active sites for solar light energy conversion. This crystal facet design of the (040)‐BVO photoanode leads to an increase in the energy conversion efficiency for solar fuel production and an enhancement of the oxygen evolution rate. The photocurrent density of the (040)‐BVO photoanode is determined to be 0.94 mA cm −2 under AM 1.5 G illumination and produces 42.1% of the absorbed photon‐to‐current conversion efficiency at 1.23 V (vs RHE, reversible hydrogen electrode). The enhanced charge separation efficiency and improved charge injection efficiency driven by (040) facet can produce hydrogen with 0.02 mmol h −1 at 1.23 V. The correlation between the (040)‐BVO photoanode and the solar fuel production is investigated. The results provide a promising approach for the development of solar fuel production using a BiVO4 photoanode. Abstract : A facile strategy for improving solar fuel production of BiVO4 photoanodes is investigated. A (040)‐crystal facet engineered BiVO4 is hydrothermally synthesized with a structure directing agent and seed layer approach. Its photocurrent density is determined to be 0.94 mA cm −2 under 1‐sun and produces 42.1% of the absorbed photon‐to‐current conversion efficiency at 1.23 V (vs RHE, reversible hydrogen electrode). The photoelectrochemical hydrogen production can reach 0.2 mmol in 10 h.